2015
DOI: 10.1136/neurintsurg-2015-011787
|View full text |Cite
|
Sign up to set email alerts
|

Metal artifact reduction for flat panel detector intravenous CT angiography in patients with intracranial metallic implants after endovascular and surgical treatment

Abstract: BackgroundFlat panel detector CT angiography with intravenous contrast agent injection (IV CTA) allows high-resolution imaging of cerebrovascular structures. Artifacts caused by metallic implants like platinum coils or clips lead to degradation of image quality and are a significant problem.ObjectiveTo evaluate the influence of a prototype metal artifact reduction (MAR) algorithm on image quality in patients with intracranial metallic implants.MethodsFlat panel detector CT after intravenous application of 80 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
3

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 34 publications
1
15
0
3
Order By: Relevance
“…Previous studies that used other MAR algorithms to evaluate intracranial metallic implants on CTA or flat-panel detector CT images observed significant improvement in the interpretation of surrounding structures. 10 11 12 13 Prell et al 10 found improved brain tissue modeling and implant visibility using an interpolation-based 3D correction algorithm for MAR; that algorithm was further modified by Psychogios et al, 11 who achieved a significant reduction of artifacts around metallic implants and improved delineation of the surrounding structures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies that used other MAR algorithms to evaluate intracranial metallic implants on CTA or flat-panel detector CT images observed significant improvement in the interpretation of surrounding structures. 10 11 12 13 Prell et al 10 found improved brain tissue modeling and implant visibility using an interpolation-based 3D correction algorithm for MAR; that algorithm was further modified by Psychogios et al, 11 who achieved a significant reduction of artifacts around metallic implants and improved delineation of the surrounding structures.…”
Section: Discussionmentioning
confidence: 99%
“… 8 9 Several studies have found that metal artifact reduction (MAR) is useful for CTA or flat-panel detector CT in patients with intracranial metallic implants. 10 11 12 13 …”
Section: Introductionmentioning
confidence: 99%
“…They found that metal artefact severity was reduced in high-keV images across changes in the metal artefact types [11]. Other study done by Pjontek et al (2015) found that contrast media and metal artefact reduction software (MARS) in angiographic CT is significantly improves image quality in patient after coiling or clipping [12]. Saake et al (2012) use intravenous contrast media in angiographic CT follow-up imaging of intracranial flow diverting device.…”
Section: Introductionmentioning
confidence: 99%
“…However, the limitations are most of the techniques do not remove all sources of streaking artefacts, cause loss of spatial resolution in images and introduce the secondary artefacts that may lead to misinterpretation [8][9][10]. Other than reconstruction technique, the use of contrast media is also proposed as metal artefact reduction technique [11][12][13]. Contrast media are a group of medical drugs used to improve the visibility of internal organs and structures in imaging techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Recent improvements in metal artifact reduction algorithms (MARA) led to a significant improvement in image appearance and post-interventional evaluation [25]. Previous studies have shown that application of a dedicated MARA in post-interventional FDCTA improves evaluation of aneurysm reperfusion, parent vessels and small vessels in the level of the implant as well as adjacent brain tissue [6].…”
Section: Introductionmentioning
confidence: 99%